Evaluation of the Validity and Reliability of Organizational Performance Measurement Techniques in Moroccan Public Academic Institutions: Effects of Collaboration and Resources - ElBachiri, Souhaila; Lehim, Hind; Driss, Daoui (Revue Internationale des Sciences de Gestion, 2025)
This article aims to reassess the reliability and validity of measurement methods, as well as the impact of partnership and resources on the organizational performance of public universities in Morocco. Data were collected from a survey of 155 managers (Presidents, Deans and General Secretaries), and the analysis focused on the 71 questionnaires collected. The methodology adopted follows the guidelines of Churchill's paradigm (1979). Our contribution focuses on the exploratory phase of the development of a scale aimed at establishing a theoretical factor structure of organizational performance. After presenting the conceptualization of this scale, the article details the procedures used to develop a multi-item scale for measuring organizational performance. The results reveal a factor structure of organizational performance, assessed through the prism of partnership and resources, which explains 63.27% of the total variance. Reliability analysis of the principal component scales shows correlation and consistency between the different items in each scale, with a reliability index (Cronbach's alpha) of 86.9%. In addition, goodness of fit is considered satisfactory, with an R2 of 50.7%.